Ethics and Equity Considerations in Electronic Resources Work: An Introduction to Basic Resources and Practices to Support Librarians during the COVID-19 Pandemic and Beyond - Craft, Anna R. (Serials review, 2021)
The COVID-19 pandemic has brought innumerable changes to the lives of individuals and institutions across the country and around the world. In this uncertain time, access to information is crucial. Electronic resources were a significant content type for libraries prior to the pandemic, and the pandemic has only increased the importance of access to these collections. With the increasing reliance on electronic content and services, some libraries are having to make rapid shifts and transitions that may change the job duties of personnel, potentially bringing new personnel into the area of electronic resources work. This column seeks to assist such personnel, particularly in the areas of ethics and equity concerns in the electronic resources field. This column reviews the literature, offers resources for further reading and consultation, and considers how the COVID-19 pandemic may be affecting these issues.